Counseling on the Practice of Al Quran Calligraphy Writing for TPA Al Muhajirin Limo Depok TPA Students - Apipudin; Adi Artino; Rudi Iskandar (Indonesian Journal of Society Development, 2023)
Dissemination of calligraphy workshop training to increase the creativity of TPA Musholla Al-Muhajirin students through workshops and calligraphy writing training. This training was attended by 50 participants specifically for TPA students who took place at the Al-Muhajirin Mosque. The results of these activities showed that some workshop participants experienced confusion when facing the practice of making calligraphy based on artistic knowledge. This workshop activity also carried out practices according to the art of calligraphy. The results of the practice carried out by the workshop participants showed that the participants experienced an increased understanding of calligraphy art material and were able to write calligraphy well